Students’ Anxiety in Presentation - Haya Haratikka; Rapat Piter Sony (Universitas Pahlawan Tuanku Tambusai, 2022)
Presentation is one of learning methods which implemented in higher education in order to train the students to have a good communication skill in the future especially in delivering their idea in front of many people. Whenever they got turn to present, the more they get anxious. The problem of this research was what the students’ anxiety in having presentation are. The purpose of this research was to find out the students’ anxieties in presentation which made them do them continuouly. This qualitative research which implemented questionaire and interview as the research intruments found that in students’ speaking anxiety there were two anxious categories, those are external and internal factors. The most factors derives from internal factor which supported by the external factors. To avoid those anxiety, students need to train themselves by reading alot to master the matery or presentation content. So they can run the presentation sucessfully now and in the future.